Juridical Review Of Default In A Motorcylcle Leasing Agreement (Research Study At. PT Adira Dinamika Multifinance, Tbk) - Yosphi Kaena (Institute Of computer Science (IOCS), 2022)
Development in a society is seen in the development of existing institutions in that society, both in the economic, social, cultural and political fields. In line with the increasing number of National Development activities, the participation of the private sector in the implementation of development will also be increased. This situation, either directly or indirectly, will demand more active activities in the financing sector. Various efforts to raise public funds have been made through the establishment of government policies. Business expansion requires financing of funds, apart from the banking system and non-bank financial institutions that are known, there are other alternative financing systems, namely: